Improving Numeracy Skills Through Games Based Learning Methods on Mathematics Learning Outcomes of Class IV SDN Pancoran 01 Pagi - Cindy Setia Agustin; Winda Amelia (Edelweiss : Journal Of Innovation In Educational Research, 2025)
This study uses the Classroom Action Research (CAR) method aimed at improving numeracy skills through games based learning in grade IV students of Pancoran 01 Pagi Elementary School with the help of a web based Wordwall application. The research subjects involved in this study were 27 students, consisting of 12 male students and 15 female students. The research technique used observation, interviews, tests, and documentation. This study was designed in cycle I and cycle II which were carried out through four stages, Planning, Implementation, Observation, and Reflection.Based on the results of data analysis during the implementation of the test at the first meeting, the pretest was obtained an average value of 55.37% of conventionally and the second meeting through games based learning carried out the posttest obtained an average value of 82.22%, thus, this study can be said to be successful because it has achieved the KKM success indicator of 75 from the results of the arithmetic test. The results of the study showed that students at meeting I were in the category of has’t improved and at meeting II were in the very good category, so that the games based learning method was more effective than conventional learning for fourth grade students of Pancoran 01 Pagi State Elementary School.